SISTEM INFORMASI AKUNTANSI PADA SIKLUS PENGGAJIAN POLITEKNIK SAINT PAUL SORONG - Liawan, Calvin; Pangkerego, Christian; Aroi, Selpince Sance (LPPM Politeknik Saint Paul Sorong, 2021)
With the help of this study, the Saint Paul Polytechnic campus' payroll accounting information system will be described. The Saint Paul Polytechnic campus served as the research subject for this study. techniques for gathering data that involve observation and documentation. By describing the payroll accounting information system that is present in the company, including payroll system activities, related functions, documents used, accounting records used, network procedures that make up the system, and internal control system, a qualitative descriptive analysis technique is used to analyze the data. The effectiveness and efficiency of the payroll process were then assessed in relation to the payroll accounting information system used at the Saint Paul Polytechnic Campus. The outcomes demonstrated that the payroll accounting information system application at the Saint Paul Polytechnic campus was successful due to the usage of a computerized system. The payroll process is therefore effectively integrated.